Bibliometric Analysis: Research Trends in the Utilization of Artificial Intelligence (AI) in Biology Learning - Rachman, Saskia Fadilla Nur (PT FORMOSA CENDEKIA GLOBAL, 2025)
The rapid development of technology in the era of the Industrial Revolution 4.0 has affected various fields, including the field of education. One of the innovations that has emerged is the use of Artificial Intelligence (AI) in biology learning. This study aims to analyze research trends related to the use of AI in biology learning with a bibliometric analysis method on 68 articles from the Scopus database. This study identifies publication patterns, research contributions, and methods used. The results of the study show that the use of AI can improve students' understanding of complex biological concepts and improve students' learning experience. In addition, AI plays an important role in assisting teachers in evaluating and assessing learning outcomes. This research provides up-to-date insights into the potential of AI in biology learning and emphasizes the importance of following technology trends to improve the quality of education.